First specimen-based Taiwanese records of Dussumieria hasseltii (Actinopterygii, Clupeiformes, Dussumieriidae) from Pingtung - Harutaka Hata; Lauren Sallan; Hsuan-Ching Ho (Acta Ichthyologica et Piscatoria)
Three specimens of the Hasselt’s rainbow sardine Dussumieria hasseltii Bleeker, 1851, collected from southwestern Taiwan, were discovered in the fish collection of National Museum of Marine Biology and Aquarium, Taiwan. Due to the previous taxonomic confusion, records of species belonging to this genus from Taiwanese waters are mostly ambiguous, and only two species, Dussumieria acuta Valenciennes, 1847 and Dussumieria modakandai Singh, Jayakumar, Kumar, Murali, Mishra, Singh et Lal, 2021, have been confirmed recently. The presently reported specimens represent the first records of D. hasseltii based on voucher-specimens from Taiwanese waters, as well as the northernmost record in the western Pacific Ocean. Detailed description and comment on the Taiwanese records are provided.